Evaluation of bone healing using rhBMP-2 soaked hydroxyapatite in ridge augmentation: a prospective observational study - Hyun-Suk Kim; Ju-Cheol Park; Pil-Young Yun; Young-Kyun Kim (SpringerOpen, 2017)
Abstract Background The goal of this study is to evaluate complication and effectiveness of alveolar ridge augmentations using a hydroxyapatite-based alloplastic bony substitute with rhBMP-2. Methods A total of 10 patients (4 males, 6 females; 58.5 ± 8.6 years) participated in this clinical research. Alveolar ridge augmentations were performed in edentulous (4 maxillary posterior, 5 mandibular posterior, and 1 mandibular anterior) regions. Anorganic bovine bone (ABB; Bio-Oss®, Geistlich Pharma AG, Wolhusen, Switzerland) was used as the bone graft material in the control group (n = 5)) while hydroxyapatite-based alloplastic bony substitute with rhBMP-2(HA+rhBMP-2; NOVOSIS®-Dent, CGBio Inc., Seongnam, Korea) was used in the experimental group (n = 5). In order to evaluate relative changes in bone volume and resorption rate of the bone graft material, CBCT radiographs were taken immediately and at 4 months after the bone graft in all subjects. Among the 10 patients, 8 received dental implants in Seoul National University Bundang Hospital, while the others received in local clinics. Bone specimens for further histomorphometric examinations were gained from these 8 patients using trephine burs during the implant placements. Clinical, radiographic, and histomorphometric evaluations were focused because of the small sample size. Results When CBCT radiographs were compared between immediately and at 4.07 ± 0.13 months after the bone graft, both alveolar bone widths (ABB 2.52 ± 0.18 mm, HA+rhBMP-2 1.75 ± 0.85 mm) and heights (ABB 1.68 ± 0.17 mm, HA+rhBMP-2 1.57 ± 0.28 mm) increased in the two groups. Resorption rates of transplanted bone graft material in the alveolar bone widths and heights were (ABB 29.7 ± 8.8%, HA+rhBMP-2 31.5 ± 7.4%) and (ABB 39.2 ± 21.8%, HA+rhBMP-2 52.6 ± 6.5%), respectively. Histomorphometrically, ABB group showed bone formation via osteoconduction and HA+rhBMP-2 group via osteoinduction. HA+rhBMP-2 group showed more bone formation around the bone graft materials than the ABB group. Postoperative complications were not found in all subjects. Conclusions Our study had following conclusions: (1) Ridge augmentations using HA+rhBMP-2 could be clinically useful to supplement implant placements in edentulous regions. (2) Serious postoperative complications related to the graft material did not occur.